My Deer Hunter: Interviews with the Cast and Creative Team - Exe Christoffersen, Erik; Krøgholt, Ida; Winkelhorn, Kathrine (Peripeti, 2023)
Interview with participants from My Deer Hunter by Christoffersen, Krøgholt og Winkelhorn. In dialouge with four participating veterans and the artistic team behind My Deer Hunter, the interview explores, how the performance and rehearsal process functioned for a group of PTSD affected veterans, and how their histories and participation in war was challenged.